IMPLEMENTATION ANALYSIS OF INDONESIA’S HEALTH SYSTEM STRENGTHENING POLICY: A CASE STUDY THE SOPHI PROGRAM AT THE MINISTRY OG HEALTH - Kunto Ariawan; Bambang Giyanto (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The Strengthening of Primary Healthcare in Indonesia (SOPHI) program is a Ministry of Health initiative to strengthen primary care and accelerate Universal Health Coverage by addressing shortages of medical equipment. Currently, only 61.07% of Community Health Centers (Puskesmas) meet the standard equipment set. Field evidence indicates targeting and duplication risks: 45% of sampled Puskesmas received equipment they had not requested, while 69% of requested items were already available—signaling a misalignment between planning and actual needs. This study aims to analyze SOPHI's policy implementation in need planning and distribution of equipment at primary facilities, and to identify factors shaping the accuracy and effectiveness of planning and to formulate policy recommendations. A qualitative, post-positivist approach was employed. Primary data were collected through in-depth interviews with purposively selected key informants (Ministry of Health, KPK, provincial/district health offices, and Puskesmas in DKI Jakarta, Garut, Jambi City, and Muaro Jambi). Secondary data comes from documents and literature reviews. Analysis followed George C. Edwards III's implementation framework—communication, resources, disposition, and bureaucratic structure. Findings show constraints rooted in: (1) incomplete and inconsistent central instructions and weak last-mile communication; (2) inaccurate needs data, limited human resources, and insufficient operational budgets for field verification; (3) opportunistic local dispositions (eg, “apply for everything”) and ASPAK data manipulation; and (4) fragmented authority and misaligned central–local structures that hinder coordination. Collectively, these factors result in mistargeting and procurement duplication. Recommendations include strengthening two-way, last-mile communication; enforcing ASPAK as a verified, tiered, single source of truth; investing in data stewardship capacity and verification budgets; fostering data integrity with clear incentives and sanctions; and realigning coordination channels (involving Kemendari, Irda, and Bappeda) to ensure integrated, needs-based provisioning.